DETERMINATION OF PREDATOR SPECIES ATTACKING SWIMMERS AT QUY NHON BAY (VIETNAM) IN 2009 AND 2010 - Quang, Vo Van; Tuan, Vo Si (Vietnam Journal of Marine Science and Technology, 2014)
The comparative analysis between the tooth marks on the bitten victim’s wound and imitated tooth marks of fish indicated that sharks but not moray eel, grouper, barracuda were subjects to attack on swimmers in Quy Nhon bay (Binh Dinh province, Vietnam) in 2009 and 2010. The analysis of the length of the gap between shark teeth and tooth marks on the bitten victim’s wound also excludes great white shark (Carcharodon carcharias) and shortfin mako (Isurus oxyrinchus) out of subjects to attack swimmers at that time. In terms of particular victims, comparison between the imitated tooth marks of the sharks with the tooth marks on the bitten victim’s wound as well as the gaps of the tooth marks, and among the molar peaks of the collected shark species could suggest that the length and distance of the bitten marks, tooth gap and shape on the body of Mr. Nguyen Quang Huynh matched those of the pigeye shark (Carcharhinus amboinensis). In case of victim Mang Duc Hanh, he is likely to be attacked by blacktip shark (Carcharhinus limbatus). The other victims could be attacked by graceful shark (Carcharhinus amblyrhynchoides). The total length of the shark which could attack on the victims is 1.37- 1.92m for graceful shark, 1.26-2.84m for blacktip shark and 1.48-2.50m for pigeye shark.